A Survey of Sedation Practices for Colonoscopy in Canada. (2011) - Porostocky, Peter; Chiba, Naoki; Colacino, Palma; Sadowski, Dan; Singh, Harminder
Abstract : BACKGROUND: There are limited data regarding the use of sedation for colonoscopy and concomitant monitoring practices in different countries. METHODS: A survey was mailed to 445 clinician members of the Canadian Association of Gastroenterology and 80 members of the Canadian Society of Colon and Rectal Surgeons in May and June 2009. RESULTS: Sixty-five per cent of Canadian Association of Gastroenterology members and 69% of Canadian Society of Colon and Rectal Surgeons members responded with the full survey. Most endoscopists reported using sedation for more than 90% of colonoscopies. The most common sedation regimen was a combination of midazolam and fentanyl. Propofol, either alone or with another drug, was used in 12% of cases. A higher proportion (94%) of adult gastroenterologists who routinely used propofol were highly satisfied compared with those using other sedative agents (45%; P<0.001). Fifty per cent of adult gastroenterologists and 29% of surgeons who were not currently using propofol expressed interest in starting to use it for routine colonoscopies. Only a single nurse was present in the endoscopy room during colonoscopy performed by two-thirds of the endoscopists. CONCLUSIONS: Results of the present survey suggest that gastroenterologists in Canada use sedation for colonoscopy in more than 90% of their patients. There was higher satisfaction among gastroenterologists who used propofol routinely for all colonoscopies. Most endoscopy rooms were staffed by a single nurse, which may limit further increases in the use of propofol. Further studies are needed to determine optimal staffing of endoscopy units with and without the use of propofol. Sedation practices of general surgery endoscopists need to be evaluated.